Soil Conservation Effects and Economic Benefit Of Different Crops Cultivated on Gentle Slopes In The South Mining Area, China (Bangladesh Journal of Botany, 2021)
The runoff and sand production of two fibre crops, Hibiscus cannabinus L. (Kenaf) and Boehmeria nivea L. (Ramie), under natural rainfall conditions in natural gentle sloping (less than 10°) farmlands in a in mining area were studied. Abelmoschus esculentus L. Moench (Okra) and Zea mays L. (Maize) plants were used as the control. The results showed the rank of soil erosion moduli and average runoff coefficients among tested plant species were: okra plot > maize plot (CK) > kenaf plot > ramie plot. Economic benefits were harvested from different crop treatments, with the maximum of 25,157 CNY/ha for kenaf,19,440 CNY/ha for ramie, 16,858.6 CNY/ha for okra, and 18,332 CNY/ha for corn (CK) treatment. Results suggest that planting kenaf and ramie on gentle slopes in eastern Hunan is beneficial to water and soil conservation and can effectively prevent soil erosion.Bangladesh J. Bot. 50(3): 755-761, 2021 (September) Special